Pendampingan dan Sosialisasi dalam Terapi Kelompok Terapeutik dalam Upaya Analisis Perkembangan Anak Usia Sekolah - Wahyuni, Sri; Belangi, Siska Putri; Hastutiningtyas, Wahidyanti Rahayu; Fadli, Khalikul (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Mental health promotion efforts are carried out throughout human life to improve the individual's ability to achieve tasks according to the stage of development. If this is not done, it will experience psychosocial development disorders. Currently, there are still many families in the community who do not understand how to stimulate the development of school-age children in several types of development such as motoric, cognitive and language, emotional and personality, moral and spiritual, and psychosocial. The purpose of this community service is to stimulate school-age children according to their stages of growth and development optimally through a therapeutic group therapy approach for school-age children. This community service activity uses an implementation method consisting of three stages, namely the preparation stage, implementation of Therapeutic Group Therapy actions consisting of five sessions and evaluation. The results of this activity showed that the majority of participants experienced an increase in the level of development well in school-age children after Therapeutic Group Therapy was carried out. Therefore, therapeutic group therapy is recommended as a promotion to stimulate optimal development that affects the mental health of school-age children in the mental health service setting in the community, especially in schools.